(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In recent years, issues of legal reform in the field of property relations, including the relations arising from the division of the property of the spouses, have been increasingly raised in scientific circles and at the legislative level. Property relations of husband and wife are regulated by civil and family legislation. Revision of the concepts of "common property of husband and wife" of the Family Code, in particular, requires clarification, development of criteria for distinguishing personal and joint obligations. The article analyzes the principles of the distribution of property of the spouses. It is said that it is necessary to expand the concept of the property of husband and wife, to include virtual objects of economic value in it. The problem of the distribution of the spouse’s debts, the abuse of the rights of the spouses in the division of common property is considered. The issues that arise in the resolution of disputes about the division of property acquired during marriage, the judicial practice in this regard is studied.